1997
DOI: 10.1111/j.1469-7793.1997.211bf.x
|View full text |Cite
|
Sign up to set email alerts
|

Forearm sympathetic withdrawal and vasodilatation during mental stress in humans

Abstract: In humans, mental stress elicits vasodilatation in the muscle vascular beds of the forearm that may be neurally mediated. We sought to determine the extent to which this vasodilatation is due to sympathetic withdrawal, active neurogenic vasodilatation, or β‐adrenergically mediated vasodilatation. We simultaneously measured forearm blood flow and muscle sympathetic nerve traffic to the forearm during mental stress in humans. In a second study, we measured forearm blood flow responses to mental stress after sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
140
5
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(160 citation statements)
references
References 23 publications
11
140
5
4
Order By: Relevance
“…These results suggest that the initial forearm vasodilatation response to stress and the reductions in forearm vascular resistance are reinforced by ␤2-adrenergic or cholinergic activity. Furthermore, Halliwell et al 25 examined skeletal muscle vasodilatation to mental stress in order to determine the extent to which this response was due to sympathetic withdrawal, active neurogenic vasodilatation, or ␤-adrenergically mediated vasodilatation. Firstly, they found that muscle sympathetic nerve activity to the forearm was inhibited during mental stress (a 2.5-min Stroop task), suggesting that sympathetic vasoconstrictor withdrawal may contribute to the vasodilatation response.…”
Section: Vascular Stress-reactivity Mechanismmentioning
confidence: 99%
“…These results suggest that the initial forearm vasodilatation response to stress and the reductions in forearm vascular resistance are reinforced by ␤2-adrenergic or cholinergic activity. Furthermore, Halliwell et al 25 examined skeletal muscle vasodilatation to mental stress in order to determine the extent to which this response was due to sympathetic withdrawal, active neurogenic vasodilatation, or ␤-adrenergically mediated vasodilatation. Firstly, they found that muscle sympathetic nerve activity to the forearm was inhibited during mental stress (a 2.5-min Stroop task), suggesting that sympathetic vasoconstrictor withdrawal may contribute to the vasodilatation response.…”
Section: Vascular Stress-reactivity Mechanismmentioning
confidence: 99%
“…Several mechanisms have been proposed. First, sympathetic withdrawal during mental stress could cause vasodilatation [Halliwill et al, 1997]. This possibility appears unlikely because mental stress has been associated with unaltered or increased mSNA.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of β 2 -adrenergic receptors could contribute to the increased expression of endothelial nitric oxide [Dawes et al, 1997;]. Furthermore, increases in arterial pressure during mental stress could augment vascular shear stress, which also stimulates synthesis and release of nitric oxide by the vascular endothelium [Halliwill et al, 1997]. Importantly, forearm resistance vessel endothelial dysfunction has been observed in uncomplicated obesity [Perticone et al, 2000].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 The skeletal muscle vasodilatation response to mental stress is thought to be mediated by both the withdrawal of sympathetic neural vasoconstrictor influences and vasodilatation by b-adrenergic pathways involving epinephrine. 49 Therefore, it is likely that the mechanisms for an attenuated postexercise vasodilatation response to stress in FH þ are linked to the sympathetic nervous system. Indeed previous studies in normal subjects have consistently demonstrated reductions in catecholamine reactivity to stress tasks (the difference in catecholamine concentration following stress compared with baseline) following an acute bout of exercise.…”
Section: Effects Of Acute Exercisementioning
confidence: 99%